Independent Commissioners as Moderators of Financial Determinants of Islamic Social Reporting: Evidence from Extractive Firms in the Jakarta Islamic Index (2019-2024) - Muhammad Syamsi Rizki; Muhammad Qamaruddin; Zaki Mubarak (At-Taradhi Jurnal Studi Ekonomi, 2025)
Islamic Social Reporting (ISR) is a form of social responsibility disclosure that not only focuses on economic aspects but also reflects Sharia values in corporate activities. This study aims to analyze the influence of profitability, leverage, institutional ownership, and firm size on ISR disclosure, as well as examine the moderating role of independent commissioners. The research employs a quantitative approach using panel data from 8 extractive sector companies listed in the Jakarta Islamic Index (JII) during the 2019–2024 period. The analysis method used is panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews 12 software. The results show that leverage has a positive and significant effect on ISR, while institutional ownership has a negative and significant effect. Profitability and firm size have no significant effect on ISR. Furthermore, independent commissioners are not able to moderate the relationship between the independent variables and ISR.